Effects of Irrigation and Nitrogen Fertilizer Input Levels on Soil NO3--N Content and Vertical Distribution in Greenhouse Tomato (Lycopersicum esculentum Mill.) - Xiukang Wang; Yingying Xing (Scientifica)
The purpose of this study is to investigate the interactions between irrigation and fertilizer treatments on soil NO3--N content and vertical distribution under drip fertigation in greenhouse tomatoes. Randomized block design with three replications and the treatments consisting of three levels of irrigation and three levels of N fertilizer were used. Three irrigation levels were W1 (100%  ET0), W2 (75%  ET0), and W3 (50%  ET0) and fertilizer levels were F1 (N240–P2O5120–K2O150 kg hm−2), F2 (N180–P2O590–K2O112.5 kg hm−2), and F3 (N120–P2O560–K2O75 kg hm−2). The result demonstrates that dynamics of soil NO3--N and its response to drip fertigation and levels of N moved toward the fore soil moist, and the average soil NO3--N content with W3 treatment was 1.23 times higher than that of the W1 treatment in 0–60 cm at 43 days after transplanting. The negative correlation between N use efficiency and levels of fertilizer N and the N recovery efficiency was increased with increases of N fertilizer application. The fertilizer nitrogen rate greatly significantly influenced soil NO3--N content. Avoiding N leaching through controlled matching N fertilizer application and controlled irrigation to tomato N demand is the key to maintain crop yield and improve N use efficiency.